2019
DOI: 10.1038/s41598-019-40324-z
|View full text |Cite
|
Sign up to set email alerts
|

Deletion of tumour necrosis factor α receptor 1 elicits an increased TH17 immune response in the chronically inflamed liver

Abstract: Tumour necrosis factor α receptor 1 (TNFR1) activation is known to induce cell death, inflammation, and fibrosis but also hepatocyte survival and regeneration. The multidrug resistance protein 2 knockout (Mdr2−/) mice are a model for chronic hepatitis and inflammation-associated hepatocellular carcinoma (HCC) development. This study analysed how the absence of TNFR1 mediated signalling shapes cytokine and chemokine production, immune cell recruitment and ultimately influences liver injury and fibrotic tissue r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 53 publications
0
9
0
Order By: Relevance
“…Whether this change in the microbiome is the result of less injury and inflammation or the driving force behind the liver damage is not clear. The deletion of TNF receptor in MDR2 KO mice (TNFR1 KO/MDR1 KO) aggravates hepatitis and fibrosis [ 245 ], and it is accompanied with increased RIPK3 but not pMLKL. RIPK3 expression correlated with the increase in CX3CR1 chemokine, and a significant increase in RIPK3 was seen in CD11b+CXCR1+ monocytes in the livers of TNFR1 KO/MDR1 KO mice, indicating a necroptosis-independent and inflammatory role for RIPK3 [ 245 ].…”
Section: Cell Death In Cholestatic Liver Diseasesmentioning
confidence: 99%
“…Whether this change in the microbiome is the result of less injury and inflammation or the driving force behind the liver damage is not clear. The deletion of TNF receptor in MDR2 KO mice (TNFR1 KO/MDR1 KO) aggravates hepatitis and fibrosis [ 245 ], and it is accompanied with increased RIPK3 but not pMLKL. RIPK3 expression correlated with the increase in CX3CR1 chemokine, and a significant increase in RIPK3 was seen in CD11b+CXCR1+ monocytes in the livers of TNFR1 KO/MDR1 KO mice, indicating a necroptosis-independent and inflammatory role for RIPK3 [ 245 ].…”
Section: Cell Death In Cholestatic Liver Diseasesmentioning
confidence: 99%
“…Recent years, increasing attention is being towards pathological immune responses in the pathogenesis of many different types of liver injuries, in which the role of Th17 and Treg cells that has been revealed gradually. Th17 cells, the recently identified pro‐inflammatory subset of CD4 + T helper cells has been proved important for the host against extracellular pathogenic substance, while, some literatures claimed that the overactivation of Th17 cells is pathogenic and closely related to the pathological processes of many liver disease 12,13 . Opposite to Th17 cells, another subset of CD4 + T cells that named regulatory T (Treg) cells are viewed as a critical immune‐suppressor in excessive inflammation responses, especially in autoimmune and inflammatory diseases 14 .…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, LI-MAIT cells produce IL-17A, which is known to activate HSCs and enhance the progression of liver fibrosis. [201][202][203] Böttcher et al showed that in AILDs, long-term stimulation of MAIT cells in the presence of IL-12 and IL-18, as well as bacterial antigens, fostered MAIT cell exhaustion due to chronic antigen exposure, although these cells expressed activation markers (CD38, HLA-DR and CD69). The exhausted phenotype was evident by the upregulation of PD-1, TIM-3, and CD39, with simultaneous increases in IFNγ expression.…”
Section: Cholangiocytes As Nonconventional Antigen-presenting Cellsmentioning
confidence: 99%